2018
DOI: 10.1155/2018/6419467
|View full text |Cite
|
Sign up to set email alerts
|

Amino Acids, Mineral Nutrients, and Efficacy of Vermicompost and Seafood and Municipal Solid Wastes Composts

Abstract: Growing medium amino acids and mineral nutrients stimulate rhizosphere activities and plant growth. A greenhouse experiment was performed to compare amino acid and mineral nutrient profiles of seafood waste compost (SFWC) and municipal solid waste compost (MSWC) and vermicompost (VC). Their efficacies were also tested on onion (Allium cepa L. "Sweet Utah"). The control was Promix-BX6 alone. The MSWC, SFWC, and VC were composed of total of 36.4, 48.3, and 67.5 mg amino acids/100 g dry weight, respectively. Glut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 16 publications
1
7
0
1
Order By: Relevance
“…Mineral nutrients composition of the municipal solid waste (MSW) compost (Table SA1) used for the present study falls within the range reported for other compost from similar sources supplied by the manufacturer and reported in Abbey et al (2018). The carbon-nitrogen (C:N) ratio of 1.72 and the concentration of the individual nutrients suggested a nutrient-dense, mature and stable MSW compost.…”
Section: Resultssupporting
confidence: 76%
“…Mineral nutrients composition of the municipal solid waste (MSW) compost (Table SA1) used for the present study falls within the range reported for other compost from similar sources supplied by the manufacturer and reported in Abbey et al (2018). The carbon-nitrogen (C:N) ratio of 1.72 and the concentration of the individual nutrients suggested a nutrient-dense, mature and stable MSW compost.…”
Section: Resultssupporting
confidence: 76%
“…The efficacy and importance of municipal solid waste compost are well documented, especially in improving soil structure, crop productivity and enhancing action transfer. [4][5][6] Nevertheless, the major concern is the potential release of heavy metals and other solid contaminants from municipal solid waste compost into soils and environment. For that matter, source separation is used to minimize contaminants, 7 while microwave technology was successfully used to extract heavy metals from sewage sludge.…”
Section: Introductionmentioning
confidence: 99%
“…humic acids, fulvic acids and humin), non-humic substances (e.gs, organic acids, amino acids, nucleic acids, mineral nutrients, carbohydrates, fatty acids, plant growth regulators, e.t.c.) and beneficial microbiome (Pena-Mendez et al, 2005;Hayes et al, 2017;Abbey et al, 2018). As a result, compost alters many fundamental plant structural, biochemical and physiological functions.…”
Section: Resultsmentioning
confidence: 99%
“…Compost is obtained from the decomposition of organic matter with a remarkably high content of microbial communities, humic and non-humic chemical substances including macro-and micro-nutrients that provide nourishment and protection to plants (Abbey, Annan, Asiedu, Oluwaseun & Iheshiulo, 2018;Steel et al, 2018). These attributes of compost may also have the potential to extend cut flower freshness and lifespan but not reported.…”
Section: Introductionmentioning
confidence: 99%